INFLATION TARGETING FRAMEWORK DAN PERUBAHAN RESPON KEBIJAKAN MONETER - Arif Setiawan (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2012)
Inflation Targeting Framework (ITF) in the last two decades becoming popular as the new framework in setting monetary policy which used inflation as nominal anchor, replacing other nominal anchor such as money growth. But its popularity was not without cristics. Opponents of ITS criticized ITF to its concern on stablization that would sacrifice other objective of policies : Output and employment. Proponents of ITF answered the critics by arguring that ITF was flexible framework rather than as rigid rule. It could anticipate problem of output in short run such during a crisis . While some research on this field found that in some ITF countries monetary policy response to inflation tended to be lower after implementing ITF, for indonesia which had implemented ITF since July 2005, how the changes in monetary policy response due to ITF implementation was an object of this research. By using taylor rule as monetary policy response function. Changes of the response measured vy changes in parameter of the model which estimated with a time varying parameter method. Evidence showed that during yhe early phase of ITF implementation the response increased very significant and tended to be what so called over shooting. The response then descreased at the next phase and looked more stabil. By an event studies : the Global Economic Crisis and the rise Of oil price, in this research we could also see how monetary otority react in dealing with those two critical event in the economy.